Introduction to Islamic Educational Philosophy: Scope, Position, and Characteristics - Mhd. Dedi Hcomaludin Jamil; Suyoto; Siti Mahmudah Nurhayati; Yahanan (Aslim: Journal of Education and Islamic Studies, 2025)
Islamic educational philosophy serves as a conceptual foundation guiding the implementation of education in accordance with Islamic values. This article aims to examine the essence, scope, position, and characteristics of Islamic educational philosophy in constructing a holistic and tawhid-oriented educational system. The study places the Qur’an and Hadith as the primary sources of thought, complemented by the perspectives of Muslim philosophers in responding to contemporary educational challenges. The discussion focuses on two main dimensions: the macro dimension, which analyzes the ontological relationship between God, human beings, and the universe; and the micro dimension, which examines educational objectives, educators, learners, curriculum, teaching methods, and educational environment. The findings indicate that Islamic educational philosophy possesses distinctive characteristics, including its foundation in revelation, orientation toward monotheism, holistic and humanistic-religious approach, normative and applicative nature, and integrative view of religious and worldly knowledge. Therefore, Islamic educational philosophy plays a strategic role as an ideological and methodological foundation in shaping the ideal human being (insan kamil) capable of addressing modern challenges without losing divine values.